Hygiene at Work: An Engineering Perspective on the Development of Hygiene Science - Peter J Pityn (Canadian Journal of Infectious Diseases and Medical Microbiology)
The present article examines the work of contemporary hygiene practitioners. Discussion converges from a broad examination of hygiene at work in our society serving the common good to occupational hygiene in the workplace. The article considers the expanding role of hygiene today, juxtaposed against the lack of awareness and perceptions of hygiene. It considers some of the current social challenges facing hygiene, perceptions of risk and problems specifically encountered by occupational hygienists.